Becoming a Culturally Proficient Teacher in These Turbulent Times - Nugent, Patricia; Crowe, Heljä Antola; Faber, Pamela (Asian Journal of Social Sciences and Management Studies, 2018)
“We teach who we are” (Palmer, 2007) is an important self-revelation. Given the current culture in America, there is much unrest in our classrooms and schools. As teacher educators, we need to be aware of the various cultures influencing not only our classrooms, but also the classrooms of our students and the society at large. This article discusses how cultural awareness and culturally proficient teaching can impact individual instructors and learning environments of their classrooms. As future teachers experience culture in our university classrooms, they are becoming aware of their own cultural identity and its effects on their future students.